(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Conventional logging practices are often highly destructive to forest ecosystems. Heavy machinery can compact the soil and destroy vegetation. Previous research by others have demonstrated that environmental damage can be minimized through the use of site- sensitive harvesting techniques. Forest harvesting in the inland forest in Malaysia is generally carried out by a combination of crawler tractor and winch lorry, which we defined as the current logging technique. Under the current logging technique, crawler tractors are used to skid logs from felling sites to skid trails and winch lorries continue the transportation to the roadside landings. In the early nineties, a Low Impact Logging (LIL) practice using an improved logging system was carried out in some forest areas in Peninsular Malaysia. The technology, called logfisher was mainly deployed to retrieve logs from rocky and deep, narrow ravine which was deemed uneconomical, difficult and dangerous for the crawler tractor to operate. In certain logging areas in Pahang, a combination of crawler tractor and logfisher is being used which we defined in this study as LIL. The study focuses on quantifying the carbon stock changes from the different logging techniques in Lipis, Pahang. Based on preliminary results, the LIL technique showed less carbon loss if the carbon stocks before and after logging were compared. This study indicates that different logging techniques results in different impact on the total residual forest carbon stocks. The introduction of LIL systems and practices have indeed reduced the logging damage and improved stand conditions. Improvement to the current practice, enhance the productivity of the residual stand and reduce forest degradation in terms of carbon stocks as well as other ecological co-benefits.